An investigation into how two Natural Science teachers in the Khomas region mediate learning of the topic of atoms and molecules in Grade 7 : a case study - Hoepfner, Narenda (Rhodes University, Faculty of Education, Department of Education, 2015)
The teaching of abstract concepts requires higher cognitive thinking skills and thus presents a challenge for most subjects in the curriculum, in particular, science subjects. Teachers often complain that they struggle to develop higher cognitive skills in learners in such topics. As a result, learners fail to understand science concepts and then complain that science is boring and hence lose interest in the subject. The main reason for this study was to investigate how Grade 7 Natural Science teachers mediate the learning of abstract topics, in particular, atoms and molecules which are regarded as the building blocks in chemistry. This study further sought to develop a teaching unit of work on atoms, molecules and the Periodic Table in partnership with the participating teachers, in order to help improve teaching and learning of the topic. The study is located within an interpretive paradigm. Within this paradigm, a qualitative case study approach was adopted whereby two Grade 7 Natural Science teachers in the Khomas Region were the research participants. This approach enabled me to seek for answers beyond the obvious classroom experiences by using document analysis, semi-structured interviews and classroom observation (which were video-taped and transcribed). The theoretical frameworks underpinning this study focused on mediation of learning and social constructivism as expounded by Vygotsky, in conjunction with Shulman's pedagogical content knowledge. Hence, emphasis was placed on the teaching strategies used by teachers, such as elicitation of prior knowledge during the lessons, language used, interaction of learners and ways how teachers deal with the challenges faced by them in the mediation of learning. An inductive analysis to discover patterns and themes was applied during the data analysis process. The themes were further turned into analytical statements to interpret the data. The validation process was achieved by using a variety of data gathering techniques. I watched the videotaped lessons with the observed teachers and I made use of member checking in the form of stimulated recall interviews and transcripts of the interviews. Thus, a summary of discussions were given back to the respondents to verify their responses and check for any misinterpretations. Different chapters of my study were given to colleagues to read through as a means of the validation process. Herein lies the importance of a critical friend in qualitative research. The findings of the study revealed that concepts of high cognitive demand should not be oversimplified when introduced to learners, as learners might find it difficult to define and conceptualise concepts as they do not have proper insights into the concepts. The findings further illuminated that teachers should develop a strong subject content knowledge as well as pedagogical content knowledge to have the best strategies in place to mediate learning of this topic. The study concludes, with Phase 2, that the exposure of and cooperation between teachers plays an indispensable role in their professional development. Essentially, this enables teachers to make use of different teaching styles as they scaffold learners in the process of making sense of, in particular, abstract science concepts. Finally, this study recommends that teachers need to engage in on-going professional development opportunities and be equipped with suitable learning support and other necessary physical resources, as a way of motivation and to be in a position to deal with all the many challenges they have to face during the mediation of learning.
Keywords: Science -- Study and teaching (Elementary) -- Namibia -- Khomas; Life sciences -- Study and teaching (Elementary) -- Namibia -- Khomas; Pedagogical content knowledge; Cognitive learning; Teachers -- In-service training -- Namibia -- Khomas